The cultural adaptation and psychometric evaluation of the Mothers on Respect Index for Native Hawaiians and Pacific Islanders - Rebecca Delafield; Eunjung Lim; Ann Chang; Crystal VangTung; Jocelyn Howard; Adrienne Dillard; Sunny Chen; Princess Lei Ebbay; Joseph Keawe'aimoku Kaholokula (BMC, 2024)
Abstract Background Native Hawaiian and Pacific Islanders (NHPI) are disproportionately burdened by pregnancy-related deaths in the United States and have the lowest engagement in prenatal care compared to all other US racial groups. Aside from access barriers, studies suggest that NHPI face challenges with patient-clinician communication, perceived discrimination, and cultural conflicts within healthcare settings. This paper describes the cultural adaptation of the 14-item Mothers On Respect index for NHPI, originally developed by Vedam et al. (2017) for diverse communities in British Columbia, Canada, and reports the findings of the preliminary psychometric assessment of the adapted measure. Methods Data from 26 interviews with NHPI women, expert, and cognitive interviews were conducted to inform the adaptation. An online survey was administered to a sample of 90 NHPI women to assess construct validity, convergent validity, and internal reliability of the adapted measure using exploratory and confirmatory factor analyses. Results The adaptation resulted in substantial changes to the original measure, mainly by the addition of items related to 'feeling cared for by and connected to the provider' and 'perceived threats hindering communication.' The psychometric analyses identified a three-factor structure for the culturally adapted index and confirmatory factor analyses were employed to refine the measure. The result was a 25-item index with acceptable goodness of fit indices, high internal reliability (Cronbach's alpha of 0.96, 95% CI = .94-.97) and convergent validity with a related scale. Overall, participants in this sample indicated high levels of respectful care; however, people who received < 8 prenatal care visits had significantly lower ratings on average. Conclusions Our findings suggest that the elements valued by NHPI are not fully captured in existing measures of respectful maternity care. Efforts to assess more discrete aspects of the patient-provider relationship for culturally distinct and racialized groups could help improve the quality of care and advance equity in maternal and perinatal health marginalized communities.